2019
DOI: 10.1111/cdev.13274
|View full text |Cite
|
Sign up to set email alerts
|

Parents Influence the Visual Learning Environment Through Children's Manual Actions

Abstract: The present research studied children in the second year of life (N = 29, M age = 21.14 months, SD = 2.64 months) using experimental manipulations within and between subjects to show that responsive parental influence helps children have more frequent sustained object holds with fewer switches between objects compared to when parents are either not involved or over-involved. Regardless of parental involvement, sustained holds were visually rich, based on the size, centeredness, and dominance of the held object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 61 publications
(102 reference statements)
1
24
0
Order By: Relevance
“…Similarly, fine motor skills such as grasping and drawing are both related as they fall under the same motor skill umbrella, but may provide very different affordances for language learning. Recent work in infants has begun to explore potential mechanisms that underlie motor-language links (Walle, 2016; West and Iverson, 2017; McQuillan et al, 2019), but further research is needed to better understand what it is about motor skills, both gross and fine, that fosters language development.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, fine motor skills such as grasping and drawing are both related as they fall under the same motor skill umbrella, but may provide very different affordances for language learning. Recent work in infants has begun to explore potential mechanisms that underlie motor-language links (Walle, 2016; West and Iverson, 2017; McQuillan et al, 2019), but further research is needed to better understand what it is about motor skills, both gross and fine, that fosters language development.…”
Section: Discussionmentioning
confidence: 99%
“…Within these processes, parental input for spatial features enhances object word learning by expanding learning episodes and providing spatial information for infants. Previous studies showed that parental responsiveness and referential language during object interaction episodes contribute to word learning (McQuillan et al, 2020; Tamis‐LeMonda et al, 2013). Furthermore, our study from a Turkish‐learning sample showed that the role of parental spatial input might be critical for object word learning during the second year of life, beyond infants' fine motor abilities.…”
Section: Discussionmentioning
confidence: 98%
“…Parents' object naming efforts become more effective in word learning at 20 months when an object dominates the visual view of an infant after holding it (Pereira, Smith, & Yu, 2014). Parents' responsive behaviours and verbal input support the sustained holding events in word learning situations (McQuillan, Smith, Yu, & Bates, 2020). Additionally, infants at the end of their first year start multimodal feedback loops with their manual exploration that trigger mothers' action‐related and informative linguistic input.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…During their developmental period children learn different behaviours and skills. In this process, they need their parents' help to cope with the difficulties they face (McQuillan et al., 2019). According to Bandura's (2004) Social Cognitive Theory (SCT), human behaviour and the environment are in interaction with each other.…”
Section: Introductionmentioning
confidence: 99%